2002
DOI: 10.1097/00003246-200201000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Adult long-segment tracheal stenosis attributable to complete tracheal rings masquerading as asthma

Abstract: Airway narrowing may masquerade as asthma. Congenital tracheal stenosis is rare and is associated with a high mortality rate. Complete tracheal rings presenting in adulthood are extremely rare, and we report the first case of long-segment pantracheal stenosis presenting in adulthood. Surgical treatment with tracheoplasty is difficult. A custom-made tracheostomy tube to stent the entire trachea is one management option. Tracheal stenosis should be excluded in patients with a chronic lack of response to therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…Our case resembles that of an adult with congenital long-segment tracheal stenosis presenting as a difficult-to-treat asthmatic [55]. The authors concluded that her episodes of asthma were in fact dynamic airway narrowing when her tracheobronchial tree was compromised further from infection and inflammation [55]. Risk factors for the development of tracheomalacia in our patient include chronic use of corticosteroids and chronic infection [50].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our case resembles that of an adult with congenital long-segment tracheal stenosis presenting as a difficult-to-treat asthmatic [55]. The authors concluded that her episodes of asthma were in fact dynamic airway narrowing when her tracheobronchial tree was compromised further from infection and inflammation [55]. Risk factors for the development of tracheomalacia in our patient include chronic use of corticosteroids and chronic infection [50].…”
Section: Discussionmentioning
confidence: 79%
“…The use of multiple antibiotics and repeated hospitalizations most likely predisposed this patient to colonization of sputum with MRSA, whereas the anatomy of this patient’s airway with narrowing and collapse of the lumen of the trachea secondary to tracheomalacia may have predisposed this adult to tracheitis. Our case resembles that of an adult with congenital long-segment tracheal stenosis presenting as a difficult-to-treat asthmatic [55]. The authors concluded that her episodes of asthma were in fact dynamic airway narrowing when her tracheobronchial tree was compromised further from infection and inflammation [55].…”
Section: Discussionmentioning
confidence: 83%
“…Many patients will experience systemic side effects of corticosteroids, such as hyperglycemia, weight gain, infections, myopathy, and/or adrenal insufficiency (7). Treatment of recurrent COPD patients begins with confirmation of the diagnosis and consideration of other conditions that mimic COPD, especially when symptoms remain despite standard medical therapy (5, 810). Our patient had advanced COPD disease (Stage D) based on her mMRC symptom score, GOLD spirometric classification, and recurrent hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…The trachea has the potential to be a "forgotten zone" in differential diagnoses, as pathological processes may not receive prominent clinical consideration as other more common disorders presenting with similar respiratory symptoms. 2 Unlike the oropharynx, this anatomical area is beyond visualization on routine inspection; unlike the mediastinum and lung fields, it is a potential "blind spot" on the routine, plain radiographic examination of the chest. 3 Nonetheless, the adult trachea is affected by a number of primary disorders and is also a target organ of a variety of systemic diseases.…”
Section: Introductionmentioning
confidence: 99%